A new primitive genus of the family Psychidae having long-scaled female antennae from the Ryukyus, Japan (Lepidoptera, Tineoidea) - Saigusa, Toyohei; Sugimoto, Mika (Zootaxa, 2022)
The Psychid genus Lepidoceropsyche Saigusa & Sugimoto, gen. nov. and its type species Lepidoceratopsyche manoi Saigusa & Sugimoto, sp. nov. (Lepidoptera, Psychidae) are described based on the female with long-scaled antennal flagella and well-developed wings from the Ryukyus, Japan.